SAMI3‐RCM simulation of the 17 March 2015 geomagnetic storm. Issue 1 (25th January 2017) - Huba, J. D.; Sazykin, S.; Coster, A.
Abstract: We present a self‐consistent modeling study of the ionosphere‐plasmasphere system response to the 17 March 2015 geomagnetic storm using the coupled SAMI3‐RCM code. The novel feature of this work is that we capture the important storm time dynamics of the ionosphere on a global scale and its manifestation in the plasmasphere. We find that the penetration electric fields associated with the magnetic storm lead to a storm time enhanced density in the low‐ to middle‐latitude ionosphere. We compare the modeled total electron content (TEC) with GPS‐measured TEC in the American sector. Additionally, we observe the development of polar cap "tongues of ionization" and the formation of subauroral plasma streams in the postsunset, premidnight sector, and its impact on the plasmasphere. However, we did not see the development of plasmaspheric plumes during this event which we attribute to the long main phase of the storm (∼18 h). Key Points: The SAMI3/RCM model captures the important storm time dynamics of the ionosphere/plasmasphere system The simulation results show the development of polar cap tongues of ionization, SAPS, and SEDs The simulation results did not see the development of a plasmaspheric plume which is attributed to the long main phase of the storm